Effectiveness of physical therapy on pain, disability and quality of life in women with lumbopelvic pain in postpartum period: a systematic review with evidence gap map and meta-analysis - Fatih Özyurt; Esra Üzelpasacı; Abdulhamit Tayfur; Türkan Akbayrak (BMC Women's Health)
Abstract Background The majority of women experience a recovery from pregnancy-related lumbopelvic pain (LPP) within three months of delivery. However, a postpartum follow-up study reported that approximately 8–20% of women still experience persistent non-specific LPP two to three years after delivery, which can interfere with daily activities. The present study aims to investigate the effect of physical therapy on pain severity, disability and quality of life in women with LPP in the postpartum period. Methods The present literature search was conducted from inception to December 2024 in the following electronic databases: PubMed, Web of Science and Cochrane Library. The inclusion criteria were met by studies written in English that were reviewed to investigate the effect of physical therapy on pain, disability, and quality of life in women over the age of 18 years old with LPP in the postpartum period. The meta-analysis was conducted using the Cochrane Review Manager software. Risk of bias was assessed using the Cochrane RoB 2 tool. A meta-analysis was performed, and the evidence levels and gaps were determined. The outcomes were also analyzed according to follow-up periods as short-term(< 3 months), mid-term(≥ 3 to 12 months) and long-term(> 12 months). Results The systematic review incorporated a total of 37 randomized controlled trials, encompassing 57 different treatment groups. These treatment groups included 1,739 women diagnosed with LPP during the postpartum period. Stabilization exercises (I2 = 92%, effect size = 2,70, 95% confidence interval (CI) = 1.87–3.54, p < 0.001 is effective in the short term with a high level of evidence. High level of evidence showed that stabilization exercises (I2 = 91%, effect size = 2.78, 95%CI = 1.87–3.69, p < 0.001) is effective in the short term. Other exercises (I2 = 87%, effect size = 1.54, 95%CI = 0.79–2.29, p < 0.001) and manipulative therapy (I2 = 98%, effect size = 10.52, 95%CI = 4.64–16.39, p = 0.0005) are effective at a moderate level of evidence in the short term. Conclusions The findings of this study indicate that the implementation of stabilization exercises is associated with a significant reduction in pain severity in the short term, a conclusion that is supported by high-quality evidence. The evidence base indicates that manipulative therapy and other forms of exercise may also contribute to a reduction in pain severity. Evidence supports the hypothesis that stabilization exercises represent the most effective intervention for reducing disability. Systematic review registration number (PROSPERO) CRD42023485978.